Horn Fly Management - Phillip E. Kaufman; Emma N. I. Weeks (EDIS)
Horn flies are one of the livestock pests with the greatest impact on the health and productivity of cattle. Economic losses due to horn fly damage are estimated at $36 million annually in Florida alone. In the U.S.A. annual losses total between $700 million and $1 billion, with up to $60 million spent on insecticidal control. Horn fly damage is caused by blood feeding. The flies feed frequently and exclusively on blood, piercing the skin of cattle with their proboscis and taking around 20 small blood meals each day. Pain and irritation due to the constant presence of the flies and their bites causes defensive behavior in the cattle that prevents adequate food consumption and rest. This 4-page fact sheet was written by P. E. Kaufman and E. N. I. Weeks, and published by the UF Department of Entomology and Nematology, September 2012.